2014
DOI: 10.1007/s11255-014-0716-z
|View full text |Cite
|
Sign up to set email alerts
|

An ignored cause of inflammation in patients undergoing continuous ambulatory peritoneal dialysis: periodontal problems

Abstract: A meticulous periodontal examination should be a routine part of management of the uremic patients on CAPD because periodontal disease could be one of the hidden sources of unexplained inflammatory status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 33 publications
3
23
0
1
Order By: Relevance
“…The study findings are consistent with other studies which show no association of periodontitis with mortality among patients with coronary artery disease and older adults [13, 32]. The lack of association between periodontitis and increased mortality among people with end-stage kidney disease has several potential explanations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The study findings are consistent with other studies which show no association of periodontitis with mortality among patients with coronary artery disease and older adults [13, 32]. The lack of association between periodontitis and increased mortality among people with end-stage kidney disease has several potential explanations.…”
Section: Discussionsupporting
confidence: 92%
“…[9, 10] Approximately 10% of adults with chronic kidney disease have evidence of moderate to severe periodontitis. [11] Periodontitis is associated with systemic inflammation [12, 13], which is implicated in the pathogenesis of cardiovascular disease caused by kidney failure [14] and such inflammation is consistently associated with worse survival in adults undergoing long-term hemodialysis [15, 16]. In our recent systematic review of dental disease in adults with chronic kidney disease [17], we identified two cohort studies that showed increased mortality among dialysis patients with periodontitis, although these studies had small sample sizes ( n  = 253 and n  = 168, respectively) and remained at risk of bias from confounding requiring additional confirmation from larger studies in the dialysis population [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…The possible causes of this association could be that males pay less attention to oral hygiene compared with females and the metabolism of the periodontal tissue was disrupted by uraemic toxins (Kocyigit et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Also in accordance with the literature, male gender, low Kt/v and URR seemed to be associated with the development of severe periodontitis in patients with CKD (Kocyigit et al . ; Hou et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Les causes de l'anorexie doivent être recherché es, parmi lesquelles il ne faut pas oublier : les pathologies buccodentaires, qui ont un rôle majeur sur le statut nutritionnel et l'inflammation, même si cela n'a pas é té spé cifiquement é tudié en dialyse pé ritoné ale [25] ; la pré sence d'une hypervolé mie, qui est un facteur de risque de dé nutrition, pré sente chez 50 % des patients en DP [13,26]. De ce fait, les apports sodé s et hydriques doivent être adapté s ; la situation socioé conomique et professionnelle, qui impacte sur le choix des aliments et le mode alimentaire ; la pré sence d'un syndrome dé pressif, qui peut avoir un impact sur le statut nutritionnel, même si cela n'a pas é té clairement mis en é vidence en DP, probablement en raison des faibles effectifs é tudié s [27] ; la lourdeur de la thé rapeutique mé dicamenteuse, qui doit é galement être prise en considé ration (nombre important de comprimé s, divers effets indé sirables).…”
Section: Parame`tres Influant Sur La Prise En Chargeunclassified